Rate-Limiting Steps in Selenium Assimilation and Volatilization by Indian Mustard - de Souza, Mark P. (American Society of Plant Physiologists, 1998)
Se can be accumulated by plants and volatilized to dimethylselenide, providing an attractive technology for Se phytoremediation. To determine the rate-limiting steps in Se volatilization from selenate and selenite, time- and concentration-dependent kinetics of Se accumulation and volatilization were studied in Indian mustard (Brassica juncea). Time-dependent kinetic studies showed that selenate was taken up 2-fold faster than selenite. Selenate was rapidly translocated to the shoot, away from the root, the site of volatilization, whereas only approximately 10% of the selenite was translocated. For both selenate- and selenite-supplied plants, Se accumulation and volatilization increased linearly with external Se concentration up to 20 μm; volatilization rates were also linearly correlated with root Se concentrations. Se-volatilization rates were 2- to 3-fold higher from plants supplied with selenite compared with selenate. Se speciation by x-ray absorption spectroscopy revealed that selenite-supplied plants accumulated organic Se, most likely selenomethionine, whereas selenate-supplied plants accumulated selenate. Our data suggest that Se volatilization from selenate is limited by the rate of selenate reduction, as well as by the availability of Se in roots, as influenced by uptake and translocation. Se volatilization from selenite may be limited by selenite uptake and by the conversion of selenomethionine to dimethylselenide.